2008
DOI: 10.1242/jeb.008649
|View full text |Cite
|
Sign up to set email alerts
|

Near- and far-field aerodynamics in insect hovering flight: an integrated computational study

Abstract: SummaryWe present the first integrative computational fluid dynamics (CFD) study of near-and far-field aerodynamics in insect hovering flight using a biology-inspired, dynamic flight simulator. This simulator, which has been built to encompass multiple mechanisms and principles related to insect flight, is capable of ʻflyingʼ an insect on the basis of realistic wing-body morphologies and kinematics. Our CFD study integrates near-and far-field wake dynamics and shows the detailed three-dimensional (3D) near-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
196
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(216 citation statements)
references
References 42 publications
17
196
2
1
Order By: Relevance
“…Under hovering flight conditions, Aono and others showed that interaction between wing and body was negligibly small: the aerodynamic force in the case with the body-wing interaction was less than 2% different from that without body-wing interaction (Aono et al, 2008;Yu and Sun, 2009). Although the left and right wings might interact via a 'clap and fling' mechanism, this mechanism was irrelevant in the present study because of small stroke amplitude.…”
Section: Computation Of Aerodynamic Forces and Power Requirementsmentioning
confidence: 54%
“…Under hovering flight conditions, Aono and others showed that interaction between wing and body was negligibly small: the aerodynamic force in the case with the body-wing interaction was less than 2% different from that without body-wing interaction (Aono et al, 2008;Yu and Sun, 2009). Although the left and right wings might interact via a 'clap and fling' mechanism, this mechanism was irrelevant in the present study because of small stroke amplitude.…”
Section: Computation Of Aerodynamic Forces and Power Requirementsmentioning
confidence: 54%
“…Most likely spanwise flow due to a pressure gradient is primarily confined to the core of the LEV. Aono and co-workers (Aono et al, 2008) further show that little spanwise flow and pressure gradient exists in the LEV of a fruit fly at Re=134, while they do find significant spanwise flow behind the LEV. For a hawkmoth at Re=6300 they did find strong spanwise flow and pressure gradient in the LEV.…”
Section: Lentink and M H Dickinsonmentioning
confidence: 93%
“…This section- by-section, quasi-two-dimensional concept of wing circulation makes the formation of two separate rings behind flapping wing pairs quite a likely outcome, and many such complicated wake structures have been reported in the insect flight literature (e.g. Aono et al, 2008;Brodsky, 1991;Grodnitsky and Morozov, 1993). However, the shedding and subsequent roll-up of shed vorticity is not easy to predict and may be very different from a quasi-two-dimensional process.…”
Section: One Ring or Two?mentioning
confidence: 93%